The Effect of Self-Healing Butterfly Hug on Anxiety Levels - Yulia Susanti; Esa Lalita Candra; Rina Anggraeni; Riani Pradara Jati; Livana PH; Amel Dawod Kamel Gouda (Universitas STRADA Indonesia, 2025)
Background: Tension refers to sensations of discomfort, anxiety, and fear, often linked to internal or external threats. Final-year students frequently encounter anxiety when working on their thesis, which can become problematic due to the intense anxiety that may negatively impact both physical and mental health. Lowering anxiety levels can be accomplished through Self Healing with the Butterfly Hug technique. Purpose: The purpose of this research was to determine the effect of Selft-Healing Butterfly Hug on students anxiety levels. Methods: The DASS questionnaire was used as the measurement tool. The study employed a Quasi-Experimental design with a One Group Pretest-Posttest Without Control format. The research sample comprised nursing students from Kendal Health Sciences College who met the specified criteria, with a total of 22 respondents selected through purposive sampling. Statistical analysis was performed using the Wilcoxon test. Results: The research results indicate that the average age of the respondents is 22 years. The majority of respondents are female, totaling 17 (77.3%). Out of the 22 respondents, the most prevalent anxiety level before the intervention was severe anxiety, reported by 12 respondents (54.5%). After the intervention, most respondents experienced moderate anxiety, with 14 respondents (63.3%). This demonstrates the impact of the Self-Healing Butterfly Hug technique on anxiety levels, as severe anxiety prior to the intervention was reduced to moderate anxiety afterward. The Wilcoxon statistical test yielded a p-value of 0.000 (p < 0.05), indicating a significant reduction in anxiety following the intervention. Conclusion: The findings of this study indicate a notable decrease in anxiety levels after applying the Self Healing Butterfly Hug technique.